Oppelzones and their heritage in current larger foraminiferal biostratigraphy. (1st April 2017) - Pignatti, Johannes; Papazzoni, Cesare A.
Abstract : The Oppelzone remains a controversial topic in stratigraphy, despite the attempts to systematize biozonal units in the International Stratigraphic Guide (ISG). In the first edition of the ISG, the Oppelzone was regarded as a particular kind of biozone, although its boundaries were recognized as 'difficult to define empirically'. This is probably the main reason why the Oppelzone was removed from the second edition of the ISG. Here, we review briefly the history and significance of the Oppelzone, starting from Jurassic zonal biostratigraphy as introduced by Oppel himself, and based mainly on ammonites, to its present usage, distinguishing the multiple meanings of the unit – biostratigraphical, chronostratigraphical, or even as a time interval. We review the Oppelzone as integral part of the current biostratigraphy of Palaeogene–Miocene larger foraminifera (the Shallow Benthic Zones, SBZ). Here, different species concepts in individual systematic groups result either in Oppelian (e.g. nummulitids, alveolinids) or non‐Oppelian (e.g. lepidocyclinids, miogypsinids and in part orthophragmines) biozones. In addition, various regional larger foraminiferal zonations have been established. These different kinds of biozones are subsumed under the biochronostratigraphical SBZ system in a similar way as regional ammonite zonations are integrated in the standard ammonite zonation. To overcome issues of fuzzy‐defined boundaries, a novel research programme is needed to: (1) establish the most suitable markers for biozonal boundaries; (2) enhance correlation with different systematic groups (especially planktonic foraminifera and calcareous nannofossils) and with other stratigraphical tools (magnetostratigraphy, radiometric dating, isotopic stratigraphy, etc.); and (3) extend morphometric criteria wherever possible to recognize the markers themselves.